Kebebasan Berpendapat dalam Media Sosial di Indonesia - Samuel Sadik Lakapu; Kotan Y. Stefanus; Hernimus Ratu Udju (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
This research aims to find out and analyze freedom of opinion in social media in Indonesia. This research is a normative research supported by empirical juridical research methods. In this study, the research approach used by the researcher is the Statute Approach, the Comparative Approach, and the Case Approach. The data of this research is sourced from primary data in the form of observations and secondary data in the form of primary, secondary and tertiary legal materials collected using literature studies and observations and this research is analyzed in a qualitative descriptive manner. The results of the study show that (1) Freedom of opinion in social media in Indonesia is an independence in expressing feelings, thoughts, ideas, and expressions in virtual form that is accommodated by digital platforms such as social media but limited by the responsibility to maintain ethics, not harm others, and follow the applicable laws and regulations in Indonesia. (2) The implementation of freedom of opinion in social media in Indonesia still faces problems due to a lack of understanding of the limits of freedom of opinion, especially in social media, such as the spread of misinformation and defamation that can trigger chaos.